Determination of the enantiomeric purity of the selective dopamine transporter inhibitor (+)‐R, R‐4‐(2‐benzhydryloxyethyl)‐1‐(4‐fluorobenzyl)piperidin‐3‐ol. Issue 6 (24th April 2017) - Neiens, Patrick; Höfner, Georg; Wanner, Klaus T.
Abstract: (+)‐ R, R ‐D‐84 ((+)‐ R, R ‐4‐(2‐benzhydryloxyethyl)‐1‐(4‐fluorobenzyl)piperidin‐3‐ol) is a promising pharmacological tool for the dopamine transporter (DAT), due to its high affinity and selectivity for this target. In this study, an analytical method to ascertain the enantiomeric purity of this compound was established. For this purpose, a high‐performance liquid chromatographic (HPLC) method, based on a cellulose derived chiral stationary phase (CSP) was developed. The method was characterized concerning its specificity, linearity, and range. It was shown that the method is suitable to determine an enantiomeric excess of up to 99.8%. With only a few adjustments, this analytical CSP‐HPLC method is also well suited to separate (+)‐ R, R ‐D‐84 from its enantiomer in a semipreparative scale. Abstract :